2015
DOI: 10.1021/acsami.5b09300
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Graphene Quantum Dots@SiO2 Nanoparticles as Electrochemiluminescence and Fluorescence Signal Indicators for Magnetically Controlled Aptasensor with Dual Detection Channels

Abstract: We proposed a facile method to prepare the nitrogen-doped graphene quantum dots (NGQDs) doped silica (NGQDs@SiO2) nanoparticles (NPs). The NGQDs@SiO2 NPs were further explored as a versatile signal indicator for ochratoxin A (OTA) aptasensing by combination with electrochemiluminescence (ECL) and fluorescence (FL) detection. In this strategy, the core-shell Fe3O4@Au magnetic beads (MBs) acted as a nanocarrier to immobilize the thiolated aptamer specific for OTA, and the amino modified capture DNA (cDNA) was ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…S2A. Three peaks at 284.58, 400.75 and 531.34 eV can be attributed to C 1s, N 1s, and O 1s, respectively (Wang et al, 2015a(Wang et al, ,2015b. The C 1 s XPS can be deconvoluted into four peaks at 284.39, 285.11, 286.53, and 288.14 eV (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…S2A. Three peaks at 284.58, 400.75 and 531.34 eV can be attributed to C 1s, N 1s, and O 1s, respectively (Wang et al, 2015a(Wang et al, ,2015b. The C 1 s XPS can be deconvoluted into four peaks at 284.39, 285.11, 286.53, and 288.14 eV (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…So, the highly sensitive and selective sensors for rapid and effective detection of NA is an extremely urgent issue concerning homeland security, environmental protection and humanitarian concerns. At present, various methods have been employed for the determination of NA, including capillary zone electrophoresis (Chen et al, 2012) and luminescent analytical methods Wang et al, 2015aWang et al, , 2015b. However, these methods reported previously suffered from limitations of complicated synthetic process, time-consuming and high operational cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table lists the application of ECL aptasensor for common toxins in food. Ochratoxin A (OTA), one kind of ochratoxins, has been extensively studied because it is a potential carcinogen . Using N ‐(4‐aminobutyl)‐ N ‐ethyl‐isoluminol (ABEI) as the ECL probe, Wang et al reported a simple ECL aptasensor for OTA with a LOD of 0.007 ng/mL .…”
Section: The Application Of Ecl Fna‐based Sensors In Food Contaminantsmentioning
confidence: 99%
“…In these ECL aptasensors, ECL probes‐labeled DNAs or targets are obtained by complex cross‐linkers and purification processes, which were time‐consuming and of low yield. The development of label‐free ECL aptasensors could overcome these drawbacks . Wang et al used Ru(phen) 3 2+ as the probe to develop an aptasensor for adenosine and lysozyme, with the linear ranges of 0.5 × 10 −9 to 7 × 10 −9 mol/L and 0.5 to 9 ng/mL, respectively.…”
Section: The Application Of Ecl Fna‐based Sensors In Food Contaminantsmentioning
confidence: 99%